Menggagas Kembali Ruang Publik Desa (Analisis terhadap Pemanfaatan Ruang Publik Pedesaan di Wilayah Kabupaten Ponorogo) - Hilman, Yusuf Adam (Jurnal The Messenger, 2017)
Utilization of public spaces for community purposes is vital, given the existence becomes a precious thing amid the urgency people to enjoy freedom in space , that public space existence is not only limited by urban areas alone, why this is so, because the public space is basically a requirement need to be met. The public space in urban areas, such as: alun-alun square, city park, playroom, anti-smoking room, as well as expressive space for the disabled. In fact if we examine, the village also has a space can be used, and its function is the same as an expressive means of urban communities, although amid the routine of farming or gardening, so it needs space, that form and concept of public space in rural areas is more modest, but the public space is a source of knowledge society.